Are cash incentives always king? A randomized controlled trial evaluating hedonic versus cash incentives (TEH-C) - Finkelstein, Eric Andrew; Chow, Michelle Tian Nee; Gandhi, Mihir (Frontiers in Public Health, 2024)
Physical inactivity is a risk factor for obesity and non-communicable diseases. Despite myriad health and non-health benefits resulting from physical activity (PA), most individuals do not meet PA recommendations. Providing an incentive for meeting activity goals may increase activity levels. Classical economists argue that cash is the best incentive. Behavioural economists have posited that hedonic (pleasurable) incentives (e.g., massages, restaurant meals) may be superior to cash when incentives are offered over multiple time periods. To date, no studies have directly compared the effectiveness of cash versus hedonic incentives in promoting PA across multiple time periods. We conducted a two-arm, parallel, 4-month randomised controlled trial with healthy adults in Singapore where participants were randomised to either cash or hedonic incentives. Participants could earn up to SGD50 (≈USD37) in cash or hedonic incentives each month they met the study’s step target of 10,000 steps daily on at least 20/25 days out of the first 28 days of a month. The primary objective was to compare the mean proportion of months that participants met the step target between the two arms. By month 4, participants in the cash (N = 154) and hedonic incentive (N = 156) arms increased their mean daily steps by 870 (p < 0.001) and 1000 steps (p < 0.001), respectively. The mean proportion of months the step target was achieved was 90.53 and 88.34 for participants in the cash and hedonic incentive arms respectively, but differences across arms were small and not statistically significant for this or any outcome assessed. Our findings suggest that both cash and hedonic incentives are effective at promoting physical activity but that neither strategy is clearly superior. NCT 04618757 (ClinicalTrials.gov) registered on November 6, 2020.